IMPLEMENTATION OF THE MONEY FOLLOW PROGRAM IN BUDGET PLANNING AT THE IMMIGRATION OFFICE CLASS II NON TPI KEDIRI - Cahyaningtyas, Riza Putri; Astuti, Rita Kusuma; Firlana, Habbi (Journal of Administration and International Development, 2023)
This study aims to determine the implementation of the Money Follow Program in budget planning at the the Immigration Office of Non-Border Control Kediri and what obstacles are faced in its application in the 2022 fiscal year. This research is a descriptive qualitative research in which data processing is obtained through observation, interviews, and documentation in the field. Based on the results of the study, the implementation of the Money Follow Program at the Immigration Office of Non-Border Control Kediri was successful in creating synergy between the facilitative and substantive sections. A holistic-thematic and integrative approach is used to align the program with national priorities. Budget realization increased from 86.95% (2021) to 98.56% (2022), with budget to performance efficiency (86.44) and IKPA (99.97). Success factors involved effective communication, adequate resource allocation, positive attitudes of implementers, and an organized bureaucratic structure. Despite the success, some obstacles still exist. Some employees do not understand the program, spending restrictions due to the PNBP Disbursement Maximum, and policy changes from the Ministry of Finance/Ministry of Law and Human Rights can affect program implementation.